Model Kepemimpinan Kepala Sekolah Berbasis Compassionate Leadership Pada Implementasi Kurikulum Merdeka (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study aims to examine and formulate a principal leadership model based on compassionate leadership in building school culture within the implementation of the Merdeka Curriculum. This research employs a qualitative approach using a library research method. Data were collected from various sources, including scholarly journals, books, and relevant educational policy documents, and were analyzed using content analysis to identify concepts, characteristics, and relationships among variables supporting school culture development. The findings reveal that principal leadership practices remain largely administrative and have not optimally contributed to strengthening a humanistic school culture. Therefore, this study proposes a compassionate leadership-based model consisting of affective, relational, and transformational dimensions as a strategic approach to building a school culture grounded in empathy, care, and collaboration. The implications indicate that implementing compassionate leadership can strengthen the role of school principals in fostering an inclusive school culture, improving students’ emotional well-being, and supporting the effective implementation of the Merdeka Curriculum.